Improving livelihood security through technological intervention on animal husbandry sector in East Champaran district of Bihar - Singh, Sanjay Kumar; Kumar, Pankaj; Kumar, Gopal; Nath, Vishal (Indian Farming, 2019)
Low income is associated with small landholdings. The Northern Bihar in general and East Champaran in particular is characterized by inaccessibility, marginality, fragility, cultural heterogeneity, rich biodiversity, low livestock and crop productivity. The residents of this district are mostly non-vegetarian. Meat of any kind of desi chicks, quail and goat is highly preferable without any religious consideration. Landless women farmers of the district involve a zero to negligible input based livestock and poultry production system but on very small scale. This system aims to get medium output from nearly zero input and mostly depends on the locally available resources. However, there are major constraints like non-availability of good poultry germplasm (breeds of Vanaraja, Grampriya or Kadaknath), lack of scientific knowledge of improved production practices (that led to less growth, prevalent unilateral paralysis of the wing or leg, lameness, unthriftiness, gray eyes, blindness and dysentery) and higher mortality deters the downtrodden farmers in going for commercial poultry farming. Like chicken, ducks are reared by women of Bahari Nazir village of East Champraran for mainly eggs and meat. They preferred rearing of Japanese quail over Vanaraja chicks due to some mishappening in the past and they have developed superstitions.